A Triboelectric Transduction Mechanism from Flow-Induced Low-frequency Structural Resonance. Issue 1 (1st February 2023) - Li, Xiaowei; Zhou, Yuan; Li, Zhongjie; Zhang, Dan; Wu, Hao; Gong, Ying; Zhang, Di; Peng, Xuzhang
Abstract: A triboelectric nanogenerator (TENG) based on the vortex-induced vibrational resonance is proposed to collect the kinetic flow energy of rivers and oceans. A prototype was fabricated to study the performance of the harvester. Experiments were conducted at flow velocities below 1 m/s. The results show that when flow velocity reaches a low level, the mechanism starts to vibrate; thus, the voltage can be generated, and the voltage increases with the growth of flow velocity. When flow velocity reaches a medium level, the structural resonance take place, resulting in the maximum amplitude of the device and voltage outputs which does not increase further with the growth of flow velocity. When flow velocity reaches a high level, the vortex-induced resonance phenomenon disappears so that amplitude and voltage decrease. The experimental results demonstrate the feasibility of using TENG to harvest vortex-induced vibration energy.